Therapeutic effect of Sheng Mai San, a traditional Chinese medicine formula, on inflammatory bowel disease via inhibition of NF-κB and NLRP3 inflammasome signaling - Lee, Magnolia Muk-Lan; Chan, Brandon Dow; Ng, Yuen-Wa; Leung, Tsz-Wing; Shum, Tan-Yu; Lou, Jian-Shu; Wong, Wing-Yan; Tai, William Chi-Shing (Frontiers in Pharmacology, 2024)
Introduction: Inflammatory bowel disease (IBD) is a globally emergent chronic inflammatory disease which commonly requires lifelong care. To date, there remains a pressing need for the discovery of novel anti-inflammatory therapeutic agents against this disease. Sheng Mai San (SMS) is a traditional Chinese medicine prescription with a long history of use for treating Qi and Yin deficiency and recent studies have shown that SMS exhibits anti-inflammatory potential. However, the effects of SMS on the gastrointestinal system remain poorly studied, and its therapeutic potential and underlying molecular mechanisms in IBD have yet to be discovered. In this study, we examined the therapeutic efficacy of SMS in IBD and its anti-inflammatory activity and underlying molecular mechanism, in vivo and in vitro. Methods: The therapeutic efficacy of SMS in IBD was assessed in the DSS-induced acute colitis mouse model. Body weight, stool consistency, rectal bleeding, colon length, organ coefficient, cytokine levels in colon tissues, infiltration of immune cells, and colon pathology were evaluated. The anti-inflammatory activity of SMS and related molecular mechanisms were further examined in lipopolysaccharide (LPS)-induced macrophages via assessment of pro-inflammatory cytokine secretion and NF-κB, MAPK, STAT3, and NLRP3 signalling. Results: SMS significantly ameliorated the severity of disease in acute colitis mice, as evidenced by an improvement in disease activity index, colon morphology, and histological damage. Additionally, SMS reduced pro-inflammatory cytokine production and infiltration of immune cells in colon tissues. Furthermore, in LPS-induced macrophages, we demonstrated that SMS significantly inhibited the production of cytokines and suppressed the activation of multiple pro-inflammatory signalling pathways, including NF-κB, MAPK, and STAT3. SMS also abolished NLRP3 inflammasome activation and inhibited subsequent caspase-1 activation and IL-1β secretion, suggesting a new therapeutic target for the treatment of IBD. These mechanistic findings were also confirmed in in vivo assays. Conclusion: This study presents the anti-inflammatory activity and detailed molecular mechanism of SMS, in vitro and in vivo. Importantly, we highlight for the first time the potential of SMS as an effective therapeutic agent against IBD.